Lithium iron phosphate positive electrode material, preparation method thereof and electrochemical device

Through the collaborative process of dry mixing and wet grinding, the production process of lithium iron phosphate positive electrode material is simplified, the problems of complex processes and high energy consumption in the existing technology are solved, and the compaction density and electrical performance of the material are improved. Suitable for mass production.

CN119191252AActive Publication Date: 2024-12-27NANTONG RESHINE NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411345629.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-27
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

The production process of existing lithium iron phosphate cathode materials is complex, has high energy consumption and low production capacity, and it is difficult to simultaneously improve the compaction density and electrical properties of the materials.

Method used

Using a collaborative process of dry mixing and wet grinding, through primary dry mixing and secondary wet grinding, the process flow is simplified, the particle size is precisely controlled, the number of grinding and spray drying is reduced, and the compaction of lithium iron phosphate positive electrode material is improved. Density and electrical properties.

Benefits of technology

It has achieved synchronous improvement in the compaction density and electrical performance of lithium iron phosphate positive electrode material, simplified the production process, reduced energy consumption and cost, solved the capacity bottleneck, and is suitable for large-scale mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191252A_ABST
    Figure CN119191252A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium iron phosphate positive electrode material, a preparation method thereof and an electrochemical device, and the preparation method of the lithium iron phosphate positive electrode material comprises the following steps: carrying out dry mixing on a phosphorus source, an iron source, a lithium source and a first carbon source to obtain a primary mixture; performing primary sintering on the primary mixture to obtain a lithium iron phosphate precursor; mixing and grinding the lithium iron phosphate precursor, a second carbon source and a solvent to obtain a secondary mixture; and carrying out secondary sintering on the secondary mixture to obtain the lithium iron phosphate positive electrode material. Through the synergistic effect of dry mixing and grinding, the dry mixing is adopted, the grinding and spray drying times are reduced, the process is optimized, the energy consumption is reduced, meanwhile, the grinding process is adopted, the particle size of the secondary mixture is accurately controlled, and the compaction density and the electrical property of the lithium iron phosphate positive electrode material are synchronously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of new energy, and specifically to a lithium iron phosphate positive electrode material and a preparation method and an electrochemical device thereof. Background Art

[0002] Lithium iron phosphate cathode materials have been widely used in power batteries and energy storage due to their excellent safety, cost-effectiveness, structural stability and long cycle life. However, the energy density of lithium iron phosphate batteries limits their development in the power battery market. The most effective way to increase the energy density of lithium iron phosphate batteries is to increase the compaction density of lithium iron phosphate cathode materials.

[0003] Generally, the purpose of increasing the compaction density of lithium iron phosphate cathode materials is to promote particle growth by increasing the sintering temperature, but this method will lead to a decrease in the electrical performance of the cathode materials. In order to achieve the simultaneous improvement of electrical performance and compaction density, the industry currently usually adopts wet mixing, wet grinding, spray drying, high-temperature sintering, air flow crushing and screening iron removal packaging processes to produce lithium iron phosphate cathode materials. In the preparation process, even two or three mixing, grinding and sintering are required. The process is complex and cumbersome, with low production capacity and high power consumption. Summary of the invention

[0004] In view of this, in order to solve at least one of the above technical problems, an embodiment of the present application provides a method for preparing a lithium iron phosphate positive electrode material.

[0005] In addition, the embodiments of the present application also provide a lithium iron phosphate positive electrode material prepared by the aforementioned preparation method and an electrochemical device using the lithium iron phosphate positive electrode material.

[0006] The present invention provides a method for preparing a lithium iron phosphate positive electrode material, which comprises the following steps:

[0007] dry-mixing a phosphorus source, an iron source, a lithium source and a first carbon source to obtain a primary mixture;

[0008] Sintering the primary mixture to obtain a lithium iron phosphate precursor;

[0009] mixing and grinding the lithium iron phosphate precursor, the second carbon source and the solvent to obtain a secondary mixture; and

[0010] The secondary mixed material is subjected to secondary sintering to obtain the lithium iron phosphate positive electrode material.

[0011] In some possible embodiments, the dry mixing is performed by using a plowshare mixer.

[0012] In some possible embodiments, the mixing conditions of the ploughshare mixer include at least one of the following features:

[0013] (1) Mixing time is 0.5h~4.0h;

[0014] (2) The frequency of the main motor of the plow is 25Hz~50Hz;

[0015] (3) The frequency of the plow blade is 10Hz to 50Hz.

[0016] In some possible embodiments, the particle size D50 of the secondary mixture is 0.4 μm to 0.6 μm;

[0017] The grinding is carried out in two steps. In the first step, the secondary mixture is ground to a particle size D50 of 1.0 μm to 2.0 μm. In the second step, the ground product of the first step is further ground to a particle size D50 of 0.4 μm to 0.6 μm.

[0018] In some possible embodiments, the particle size distribution of the secondary mixture satisfies the following relationship: 0.90≤(D90-D10) / D50≤1.70.

[0019] In some possible embodiments, the mass percentage of the first carbon source in the primary mixture is 4% to 8%;

[0020] The mass percentage of the second carbon source in the secondary mixture is 4% to 20%.

[0021] In some possible embodiments, doping materials are further added to the primary mixed material and / or the secondary mixed material, and the doping materials include at least one of titanium dioxide, tetrabutyl titanate, magnesium oxide, magnesium acetate, magnesium hydroxide, magnesium nitrate, zirconium nitrate, zirconium hydroxide, zirconium oxide and niobium pentoxide.

[0022] In some possible embodiments, the conditions of the primary sintering include: a sintering temperature of 600° C. to 750° C., a sintering time of 3 h to 15 h, and a heating rate of 2° C. / min to 5° C. / min;

[0023] The conditions of the secondary sintering include: a sintering temperature of 700° C. to 800° C., a sintering time of 3 h to 15 h, and a heating rate of 2° C. / min to 5° C. / min.

[0024] The embodiment of the present application also provides a lithium iron phosphate positive electrode material, which is prepared by the aforementioned method for preparing the lithium iron phosphate positive electrode material.

[0025] An embodiment of the present application also provides an electrochemical device, which includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet includes the aforementioned lithium iron phosphate positive electrode material.

[0026] Compared with the prior art, the preparation method of the lithium iron phosphate positive electrode material provided in the embodiment of the present application is prepared by dry mixing and wet grinding. The lithium iron phosphate positive electrode material is prepared by the synergistic effect, wherein the preparation of the primary mixture adopts dry mixing rather than wet grinding, and the raw materials are uniformly mixed without adding solvent, which reduces the number of grinding and spray drying in the entire preparation process, simplifies the production process, improves production efficiency, and reduces energy consumption and production costs; the preparation of the secondary mixture is coordinated with the wet grinding process, which can accurately control the particle size of the secondary mixture, shorten the propagation path of lithium ions, and realize the improvement of the compaction density and electrical properties of the lithium iron phosphate positive electrode material, and improve the energy density of the lithium iron phosphate positive electrode material. The preparation method of the lithium iron phosphate positive electrode material provided in the embodiment of the present application is simple in process, can achieve the simultaneous improvement of the compaction density and electrical properties of the positive electrode material, and has high production capacity and low cost, which can effectively solve the production capacity bottleneck of the lithium iron phosphate positive electrode material production. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 A process flow chart of a method for preparing a lithium iron phosphate positive electrode material provided in an embodiment of the present application.

[0028] Figure 2 A schematic diagram of the structure of the electrochemical equipment of the lithium iron phosphate positive electrode material provided in an embodiment of the present application.

[0029] Figure 3 This is a scanning electron microscope image of the lithium iron phosphate precursor in Example 1 of the present application.

[0030] Figure 4 This is a scanning electron microscope image of the lithium iron phosphate positive electrode material in Example 1 of the present application.

[0031] Figure 5 This is a particle size distribution diagram of the lithium iron phosphate positive electrode material in Example 1 of the present application.

[0032] Figure 6 This is a scanning electron microscope image of the lithium iron phosphate positive electrode material in Comparative Example 1 of the present application.

[0033] Figure 7 This is a scanning electron microscope image of the lithium iron phosphate positive electrode material in Comparative Example 2 of the present application. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0035] For this reason, please see Figure 1 As shown, the present application embodiment provides a method for preparing a lithium iron phosphate positive electrode material, the preparation method comprising the following steps:

[0036] Step S1, dry-mixing a phosphorus source, an iron source, a lithium source and a first carbon source to obtain a primary mixture.

[0037] Specifically, the phosphorus source, iron source, lithium source and the first carbon source are dry mixed in a certain proportion to obtain a uniformly mixed primary mixture. Dry mixing can achieve efficient mixing of materials without the need for a liquid medium (or solvent), and can also crush and evenly disperse larger particles. Dry mixing, as an efficient and simple pre-treatment step, can effectively reduce the number of grinding and drying processes in the production and preparation of lithium iron phosphate, optimize the process, and reduce energy consumption. At the same time, the first carbon source in the primary mixture can be used to prepare a lithium iron phosphate precursor through thermal reduction in the next sintering process, promoting the formation of a lithium iron phosphate crystal phase structure.

[0038] In some embodiments, dry mixing can be performed by a plowshare mixer. The plowshare mixer generates strong shear and stirring forces in the material through plowshare-shaped blades, which can effectively mix the material. At the same time, compared with high-efficiency mixers, vibration mixers, drum mixers or V-type mixers, the shear force generated by the plowshare mixer can better crush and disperse the material, which is conducive to further controlling the particle size of the material.

[0039] In some embodiments, the mixing time of the plowshare mixer can be 0.5h to 4.0h. The mixing effect of the materials can be further improved within the above time range. The mixing time can further be 2h to 4h, and illustratively can be 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h or 4h, etc.

[0040] In some embodiments, the frequency of the main motor of the coulter can be 25Hz to 50Hz. The frequency of the main motor of the coulter determines the rotation speed of the coulter mixer, thereby affecting the stirring intensity of the coulter and the fluidity of the material. The frequency of 25Hz to 50Hz can increase the stirring intensity and further improve the mixing effect. The frequency of the main motor of the coulter can further be 35Hz to 50Hz, and can be 25Hz, 30Hz, 35Hz, 40Hz, 45Hz or 50Hz, etc.

[0041] In some embodiments, the frequency of the coulter blade can be 10 Hz to 50 Hz. The frequency of the blade determines the rotation speed of the blade, thereby affecting the dispersion degree and mixing effect of the material. The frequency of the blade of 10 Hz to 50 Hz can refine the material particles and further improve the dispersion of the material. The frequency of the coulter blade can further be 10 Hz to 30 Hz, and can be 10 Hz, 15 Hz, 20 Hz, 25 Hz, 30 Hz, 35 Hz, 40 Hz, 45 Hz or 50 Hz, etc.

[0042] In some embodiments, the first carbon source may include at least one of glucose, sucrose, starch, polyethylene glycol, and the like.

[0043] In some embodiments, the mass percentage of the first carbon source in the primary mixture can be 4% to 8%, and the low carbon source content of 4% to 8% can effectively improve the crystal quality and consistency of the lithium iron phosphate precursor. The mass percentage of the first carbon source in the primary mixture can further be 4% to 6%, and can be 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5% or 8%, etc.

[0044] In some embodiments, the phosphorus source may include at least one of iron phosphate and lithium dihydrogen phosphate.

[0045] In some embodiments, the iron source may include at least one of iron oxide and iron phosphate, and the like.

[0046] In some embodiments, the lithium source may include at least one of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, and the like.

[0047] In some embodiments, the molar ratio of Li:Fe:P in the phosphorus source, iron source and lithium source can be (1.0-1.05):1:(1.015-1.036). By controlling the ratio of the materials, it is beneficial to generate high-purity lithium iron phosphate positive electrode materials and reduce the risk of incomplete reaction of the materials. The molar ratio of Li:Fe:P in the phosphorus source, iron source and lithium source can further be (1.02-1.04):1:(1.015-1.036), and can be 1:1:1.015, 1.02:1:1.015, 1.039:1:1.032 or 1.045:1:1.036, etc.

[0048] In some embodiments, doping materials may be added to the primary mixed material for dry mixing, and the doping materials may include at least one of titanium dioxide, tetrabutyl titanate, magnesium oxide, magnesium acetate, magnesium hydroxide, magnesium nitrate, zirconium nitrate, zirconium hydroxide, zirconium oxide, and niobium pentoxide. The addition of doping materials is beneficial to improving the electrochemical performance, structural stability, thermal stability and other properties of the lithium iron phosphate positive electrode material, so as to further improve the comprehensive performance of the lithium iron phosphate positive electrode material.

[0049] In some embodiments, the mass of the metal in the doping material can account for 0.15% to 0.45% of the mass of the primary mixed material, and the appropriate doping amount is conducive to further optimizing the performance of the lithium iron phosphate positive electrode material. The mass of the metal in the doping material can further account for 0.3% to 0.45% of the mass of the primary mixed material, and can be 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4% or 0.45% by way of example.

[0050] Step S2, sintering the primary mixture to obtain a lithium iron phosphate precursor.

[0051] Specifically, the primary mixture is sintered once to react and generate a crystal phase structure of lithium iron phosphate to obtain a lithium iron phosphate precursor.

[0052] In some embodiments, the primary sintering temperature may be 600°C to 750°C. Within the above temperature range, it is beneficial to promote the formation of lithium iron phosphate crystal phase and control the growth of particles. The temperature may further be 650°C to 750°C, and may be 600°C, 650°C, 750°C or 750°C, etc.

[0053] In some embodiments, the time of a sintering may be 3 hours to 15 hours, and the above sintering time may ensure that the sintering reaction is fully carried out. The time may further be 5 hours to 12 hours, and may be 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours or 15 hours, etc.;

[0054] In some embodiments, the heating rate of the primary sintering may be 2°C / min to 5°C / min, which is conducive to uniform heating, avoiding excessive thermal stress, and preventing agglomeration caused by rapid heating. The heating rate may further be 3°C / min to 5°C / min, and may be 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, or 5°C / min, etc.

[0055] In some embodiments, the primary sintering atmosphere may be an inert gas atmosphere, which may include at least one of nitrogen, argon, and helium, which helps prevent oxidation of the lithium iron phosphate precursor and improve crystallinity.

[0056] In some embodiments, the particle size D50 of the lithium iron phosphate precursor is 2.0 μm to 8.0 μm, and can further be 3.0 μm to 6.0 μm, and can be 2.0 μm, 3.0 μm, 4.0 μm, 4.5 μm, 5.0 μm, 5.5 μm, 6.0 μm, 7.0 μm or 8.0 μm, etc.

[0057] Step S3, mixing and grinding the lithium iron phosphate precursor, the second carbon source and the solvent to obtain a secondary mixture.

[0058] Specifically, the lithium iron phosphate precursor, the second carbon source and the solvent are uniformly mixed and ground to effectively control the particle size of the secondary mixture, thereby increasing the compaction density of the lithium iron phosphate. In addition, since the dry mixing pretreatment has been adopted in step S1, the grinding treatment only needs one time to achieve the grading effect of large and small particles, reducing the process steps such as grinding and drying, simplifying the process and reducing energy consumption.

[0059] The second carbon source in the secondary mixture mainly functions to form a coating layer on the surface of the lithium iron phosphate positive electrode material during the subsequent sintering process and to control the particle size of the lithium iron phosphate positive electrode material.

[0060] In some embodiments, the particle size D50 of the secondary mixture is 0.4 μm to 0.6 μm, and the lithium iron phosphate precursor particles obtained after the first sintering are relatively large, and grinding can accurately control the particle size of the secondary mixture. The particle size distribution of the secondary mixture in the above range forms a particle size distribution, thereby further improving the compaction density of the lithium iron phosphate positive electrode material. At the same time, the secondary mixture with a particle size in this range shortens the lithium ion transmission path, which is beneficial to the improvement of the rate performance of the lithium iron phosphate positive electrode material, and further improves the comprehensive performance of the lithium iron phosphate positive electrode material. The particle size D50 of the secondary mixture can further be 0.5 μm to 0.6 μm, and can be exemplarily 0.4 μm, 0.42 μm, 0.45 μm, 0.48 μm, 0.5 μm, 0.52 μm, 0.55 μm, 0.58 μm or 0.6 μm, etc.

[0061] In some embodiments, in step S3, the grinding is wet grinding, and a liquid medium (or solvent) is added to disperse the lithium iron phosphate precursor and the second carbon source, which is beneficial to further obtain a uniform particle distribution and reduce the particle size. Furthermore, the liquid medium can be water, and the mass of the liquid medium can be 40% to 70% of the total mass of the secondary mixture.

[0062] In some embodiments, grinding can be carried out in two steps. In the first step, the secondary mixture is ground to a particle size D50 of 1.0 μm to 2.0 μm, and in the second step, the ground product of the first step is further ground to a particle size D50 of 0.4 μm to 0.6 μm. By grinding in steps, the grinding conditions can be optimized at each stage, the over-grinding phenomenon can be reduced, the particle size can be accurately controlled, and energy consumption can be further reduced and grinding efficiency can be improved. Exemplarily, the grinding can be carried out by introducing the material into a sand mill, first coarse grinding (the diameter of the added zirconium beads is 0.6 mm) to 1.0 μm to 2.0 μm, and then fine grinding (the diameter of the added zirconium beads is 0.3 mm) to 0.4 μm to 0.6 μm.

[0063] In some embodiments, the particle size distribution of the secondary mixture can satisfy the following relationship: the particle size distribution satisfies 0.90≤(D90-D10) / D50≤1.70. Specifically, it can be 0.90, 0.95, 1.1, 1.2, 1.35, 1.52 or 1.63, etc., and of course it can also be other values ​​within the above range, which are not limited here. The particle size distribution of the secondary mixture is within the above range. There are large particles with larger particle sizes and small particles with smaller particle sizes in the secondary mixture. The large particles and small particles can cooperate with each other to form a particle size grading. The small particles fill the pores between the large particles, and the compaction density of the lithium iron phosphate positive electrode material is further improved through the stacking effect.

[0064] In some embodiments, the second carbon source may include at least one of glucose, sucrose, starch, polyethylene glycol, etc. Exemplarily, it may be a mixture of glucose and polyethylene glycol.

[0065] In some embodiments, the mass percentage of the second carbon source in the secondary mixture can be 4% to 20%, and the carbon source content of 4% to 20% helps to form a uniform carbon layer coating, reduce the generation of free carbon, improve the conductivity of the lithium iron phosphate positive electrode material, and further improve the particle size of the lithium iron phosphate positive electrode material. The mass percentage of the second carbon source in the primary mixture can further be 8% to 18%, and can be 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, etc.

[0066] In some embodiments, doping materials may also be added to the secondary mixed material, and the doping materials may include at least one of titanium dioxide, tetrabutyl titanate, magnesium oxide, magnesium acetate, magnesium hydroxide, magnesium nitrate, zirconium nitrate, zirconium hydroxide, zirconium oxide, and niobium pentoxide. The addition of doping materials in this step can further inhibit the abnormal growth of particles, further control the particle size of the lithium iron phosphate positive electrode material, and improve the uniformity of carbon coating in the subsequent sintering step.

[0067] In some embodiments, the mass of the metal in the doping material added in this step can account for 0.05% to 0.3% of the mass of the secondary mixed material, and the appropriate doping amount is conducive to further controlling the particle size of the lithium iron phosphate positive electrode material and improving the coating effect. The mass of the metal in the doping material can further account for 0.1% to 0.2% of the mass of the secondary mixed material, and can be 0.05%, 0.1%, 0.15%, 0.2%, 0.25% or 0.3%, etc.

[0068] In some embodiments, after the lithium iron phosphate precursor is mixed and ground with the second carbon source, the secondary mixture can be spray dried. The spray drying air inlet temperature can be 220°C to 260°C, and the air outlet temperature can be 85°C to 110°C. Spray drying is conducive to the volatilization of impurities and liquid media added in wet grinding. Setting the range of the air inlet temperature and the air outlet temperature helps to control the volatilization speed and drying degree of the liquid medium and impurities during the spray drying process. A higher air inlet temperature can accelerate volatilization, while a lower air outlet temperature helps to reduce liquid residue.

[0069] Step S4, performing secondary sintering on the secondary mixed material to obtain a lithium iron phosphate positive electrode material.

[0070] Specifically, the secondary mixture is subjected to secondary sintering, and then post-processed to perform air flow crushing, screening and iron removal to obtain lithium iron phosphate positive electrode material. Secondary sintering can be carbon coated on the basis of the lithium iron phosphate precursor to improve the conductivity of the lithium iron phosphate positive electrode material; it can also improve the particle crystallinity of the lithium iron phosphate positive electrode material, thereby solving the problem of abnormal growth of primary particles that may occur in the primary sintering or sand milling process; in addition, it can also improve the stability of the lithium iron phosphate positive electrode material and reduce the risk of poor stability of the lithium iron phosphate positive electrode material due to poor stability of the raw iron source and phosphorus source. This step can effectively control the size distribution of the lithium iron phosphate positive electrode material particles, reduce crystal defects, and improve overall performance.

[0071] In some embodiments, the secondary sintering temperature may be 700°C to 800°C. Within the above temperature range, it is beneficial to further improve the particle crystallinity of the lithium iron phosphate positive electrode material. The temperature may further be 750°C to 800°C, and may be 700°C, 720°C, 750°C, 780°C or 800°C, etc.

[0072] In some embodiments, the secondary sintering time may be 3 hours to 15 hours, which is conducive to the full sintering reaction. The time may further be 5 hours to 12 hours, and may be 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours or 15 hours, etc.;

[0073] In some embodiments, the heating rate of the secondary sintering can be 2°C / min to 5°C / min, which is conducive to uniform heating, avoiding excessive thermal stress, and preventing agglomeration caused by rapid heating. The heating rate can further be 3°C / min to 5°C / min, and can be exemplarily 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min or 5°C / min, etc.

[0074] In some embodiments, the atmosphere of the secondary sintering may be an inert gas atmosphere, which may include at least one of nitrogen, argon and helium, which helps prevent oxidation of the lithium iron phosphate positive electrode material and improves crystallinity.

[0075] Compared with the prior art, the preparation method of the lithium iron phosphate positive electrode material provided in the embodiment of the present application has the following beneficial effects:

[0076] 1. Through the synergistic effect of dry mixing and wet grinding, compared with the industry's high compaction density lithium iron phosphate positive electrode material preparation method using two wet grinding, the low-energy dry mixing is used instead of one high-energy wet grinding, which reduces the number of grinding and spray drying, simplifies the production process, and improves production efficiency; at the same time, the combination of one wet grinding can accurately control the particle size of the secondary mixture, achieving a simultaneous improvement in the compaction density and electrical properties of the lithium iron phosphate positive electrode material.

[0077] 2. Using a plowshare mixer for dry mixing can utilize the shear force and stirring force generated by the plowshare mixer to better mix, crush and disperse the materials, which is beneficial to further control the particle size of the materials.

[0078] 3. The grinding step can control the particle size distribution of the secondary mixture particles, achieve particle size grading of large and small particles, and further improve the compaction density of the lithium iron phosphate positive electrode material; the grinding step can also further reduce energy consumption and improve grinding efficiency by step-by-step grinding.

[0079] 4. By adding the first carbon source to the primary mixture, the formation of a lithium iron phosphate crystal phase structure is promoted; by adding the second carbon source to the secondary mixture, a coating layer is formed on the surface of the lithium iron phosphate positive electrode material during the sintering process in step S4, which is also conducive to controlling the particle size of the lithium iron phosphate positive electrode material. The effects of the first carbon source and the second carbon source can also be further improved by adjusting the addition amounts of the first carbon source and the second carbon source.

[0080] 5. The preparation method of the present application has a simple process, high production capacity and low cost, which can effectively solve the production capacity bottleneck in the production of lithium iron phosphate positive electrode materials and is conducive to the large-scale batch production of lithium iron phosphate positive electrode materials.

[0081] The present application also provides a lithium iron phosphate positive electrode material, which is prepared by the above-mentioned positive electrode material preparation method. Compared with the prior art, the lithium iron phosphate positive electrode material provided by the present application has good electrochemical performance and compaction density, and has low cost.

[0082] In some embodiments, the compaction density of the lithium iron phosphate positive electrode material can be 2.52 g / cm 3 ~2.57g / cm 3 , a higher compaction density is conducive to the improvement of the energy density of lithium iron phosphate positive electrode materials. The compaction density of lithium iron phosphate positive electrode materials can be further 2.55g / cm 3 ~2.57g / cm 3 , which can be 2.52 g / cm 3 , 2.53g / cm 3 , 2.54g / cm 3 , 2.55g / cm 3 , 2.56g / cm 3 or 2.57 g / cm 3 wait.

[0083] In some embodiments, the resistivity of the lithium iron phosphate positive electrode material may be 22Ω·cm to 40Ω·cm. The lower internal resistance of the lithium iron phosphate positive electrode material helps to improve the power density, charge and discharge efficiency, and thermal stability of the manufactured battery.

[0084] See also Figure 2 As shown, an embodiment of the present application provides an electrochemical device (e.g., a battery), wherein the electrochemical device 100 includes a positive electrode sheet 10, a negative electrode sheet 20, a separator 30, and an electrolyte 40, wherein the separator 30 is disposed between the positive electrode sheet 10 and the negative electrode sheet 20, and the positive electrode sheet 10 includes the aforementioned positive electrode material.

[0085] Compared with the prior art, the electrochemical device 100 provided in the embodiment of the present application adopts the aforementioned positive electrode material. Since the positive electrode plate of the electrochemical device 100 contains the above-mentioned high-density, low-resistance lithium iron phosphate positive electrode material, the electrochemical device 100 has good energy density, power density, charge and discharge efficiency, thermal stability and other properties, and is safe, efficient and low-cost.

[0086] The above-mentioned lithium iron phosphate positive electrode material and its preparation method are further described below through specific examples.

[0087] Example 1

[0088] Step 1: Add 100 kg of iron phosphate, 25 kg of lithium carbonate, 6 kg of glucose and 525.5 g of titanium dioxide into a plowshare mixer, wherein the molar ratio of Li:Fe:P is 1.039:1:1.032, and mix in the plowshare mixer for 0.5 to 4.0 hours, with the plowshare main motor frequency of 40 Hz and the fly cutter frequency of 15 Hz to obtain a primary mixture.

[0089] Step 2: sinter the primary mixture under nitrogen atmosphere protection conditions, raise the temperature to 650° C. at a rate of 2.5° C. / min, keep the temperature for 7.5 hours, and finally cool it down to obtain a lithium iron phosphate precursor.

[0090] Step 3, 100kg of the lithium iron phosphate precursor, 3.5kg of glucose, 6.0kg of polyethylene glycol (molecular weight 6000), 333.7g of titanium dioxide and 136kg of water were mixed and stirred evenly, and the mixture was introduced into a sand mill for coarse grinding (zirconium bead diameter 0.6mm), the first grinding particle size D50 = 1.68μm, and then introduced into a sand mill for fine grinding (zirconium bead diameter 0.3mm), the grinding particle size D50 = 0.56μm, (D90-D10) / D50 = 1.35, to obtain a secondary mixture. The secondary mixture was then spray dried, the spray drying air inlet temperature was 240°C, and the air outlet temperature was 95°C.

[0091] Step 4: sinter the dried secondary mixture under inert atmosphere protection conditions, raise the temperature to 780°C at a rate of 2.5°C / min, keep warm for 7.5 hours, cool, and finally perform air flow crushing and sieving to remove iron to obtain lithium iron phosphate positive electrode material.

[0092] Example 2

[0093] The specific process of the preparation process refers to Example 1. The difference from Example 1 is that the particle size D50 of the secondary mixture after fine grinding in step 3 is 0.42 μm, (D90-D10) / D50 is 0.91, and the preparation method of the remaining lithium iron phosphate positive electrode materials is basically the same as that in Example 1, which will not be described in detail here.

[0094] Example 3

[0095] The specific process of the preparation process refers to Example 1. The difference from Example 1 is that the particle size D50 of the secondary mixture after fine grinding in step 3 is 0.68 μm, (D90-D10) / D50 is 1.37, and the preparation method of the remaining lithium iron phosphate positive electrode materials is basically the same as that in Example 1, which will not be described in detail here.

[0096] Comparative Example 1

[0097] Step 1: 100 kg of ferric phosphate, 25 kg of lithium carbonate, 8.5 kg of glucose, 2.6 kg of polyethylene glycol (molecular weight 6000), 525.5 g of titanium dioxide and 142 kg of water are mixed evenly, wherein the molar ratio of Li:Fe:P is 1.039:1:1.032, and the mixture is introduced into a sand mill for coarse grinding (zirconium bead diameter 0.6 mm), and the first grinding particle size D50 = 1.86 μm, and then introduced into a sand mill for fine grinding (zirconium bead diameter 0.3 mm), and the grinding particle size D50 = 0.46 μm, (D90-D10) / D50 = 1.30, to obtain a primary mixture. The primary mixture is then spray dried, and the spray drying air inlet temperature is 220°C and the air outlet temperature is 90°C.

[0098] Step 2: sinter the dried primary mixture under inert atmosphere protection conditions, raise the temperature to 780°C at a rate of 2.5°C / min, keep the temperature for 7.5 hours, cool it down, and finally perform air flow crushing and sieving to remove iron to obtain lithium iron phosphate positive electrode material.

[0099] Comparative Example 2

[0100] Step 1: 100 kg of ferric phosphate, 25 kg of lithium carbonate, 6 kg of glucose, 525.5 g of titanium dioxide and 142 kg of water are mixed evenly, wherein the molar ratio of Li:Fe:P is 1.039:1:1.032, and the mixture is introduced into a sand mill for coarse grinding (zirconium bead diameter 0.6 mm), and the first grinding particle size D50 = 1.86 μm, and then introduced into a sand mill for fine grinding (zirconium bead diameter 0.3 mm), and the grinding particle size D50 = 1.0 μm to obtain a primary mixture. The primary mixture is then spray dried, and the spray drying air inlet temperature is 220°C and the air outlet temperature is 90°C.

[0101] Step 2: sinter the dried primary mixture under inert atmosphere protection conditions, raise the temperature to 650° C. at a rate of 2.5° C. / min, keep the temperature for 7.5 hours, and cool down to obtain a lithium iron phosphate precursor.

[0102] Step 3, 100kg of the lithium iron phosphate precursor, 3.5kg of glucose, 6.0kg of polyethylene glycol (molecular weight 6000), 333.7g of titanium dioxide and 136kg of water were mixed and stirred evenly, and the mixture was introduced into a sand mill for coarse grinding (zirconium bead diameter 0.6mm), the first grinding particle size D50 = 1.68μm, and then introduced into a sand mill for fine grinding (zirconium bead diameter 0.3mm), the grinding particle size D50 = 0.57μm, (D90-D10) / D50 = 1.07, to obtain a secondary mixture. The secondary mixture was then spray dried, the spray drying air inlet temperature was 220°C, and the air outlet temperature was 90°C.

[0103] Step 4: sinter the dried secondary mixture under inert atmosphere protection conditions, raise the temperature to 750°C at a rate of 2.5°C / min, keep warm for 7.5 hours, cool, and finally perform air flow crushing and sieving to remove iron to obtain lithium iron phosphate positive electrode material.

[0104] The process parameters of the above embodiments and comparative examples are shown in Table 1.

[0105] The energy consumption test method is as follows: according to the theoretical output of lithium iron phosphate positive electrode material, calculate the power consumption (kWh / t) generated by sanding and spraying;

[0106] The gas consumption test method is: according to the theoretical output of lithium iron phosphate positive electrode material, calculate the gas consumption (m 3 / t).

[0107] Table 1

[0108]

[0109] The lithium iron phosphate positive electrode materials obtained in Example 1-3 and Comparative Example 1-2 were subjected to the following tests, and corresponding test results were obtained.

[0110] 1. The pH value, specific surface area, carbon content, powder compaction density, resistivity and electrical properties of the lithium iron phosphate positive electrode materials obtained in Examples 1-3 and Comparative Examples 1-2 were tested. The results are shown in Table 2.

[0111] (1) Specific surface area: Using the nitrogen adsorption-desorption method, at liquid nitrogen temperature, the equilibrium adsorption amount of nitrogen on the surface of an object is related to its specific surface area and other characteristics. Combined with the law of change of adsorption amount with relative pressure during the adsorption process, the specific surface area test can be carried out.

[0112] (2) Carbon content: The carbon content of lithium iron phosphate positive electrode material is tested by infrared analysis. The sample is burned in a high-temperature, oxygen-rich state using a carbon-sulfur analyzer. The carbon element contained in the sample is oxidized into carbon dioxide and enters the infrared detector with the carrier gas. The carbon content is calculated by quantitatively analyzing the changes in the intensity of the infrared absorption wavelength of the carbon dioxide signal.

[0113] (3) Powder compaction density: The test is conducted in accordance with the method specified in the standard drafted by the National Technical Committee for Standardization of Nonferrous Metals, "Determination of compaction density of lithium-ion battery positive electrode material powder".

[0114] (4) Powder resistivity test: The test was conducted in accordance with the method specified in the standard drafted by the National Technical Committee for Standardization of Nonferrous Metals, "Determination of Powder Resistivity of Lithium-ion Battery Positive Electrode Materials".

[0115] (5) Electrical performance test: The lithium iron phosphate positive electrode materials in Examples 1-3 and Comparative Examples 1-2 were made into positive electrode sheets for button-type battery assembly. Metallic lithium was used as the negative electrode material. The assembled button-type battery was tested within a voltage range of 2.0 to 3.75 V.

[0116] The test steps for the first charge and discharge efficiency include: at a normal temperature of 25°C, charging the lithium-ion battery at a constant current of 0.1C to 3.75V, then charging at a constant voltage until the current drops to 0.05C, stopping charging, and recording the first charge capacity; then discharging at 0.1C to a cut-off voltage of 2.0V, recording the first discharge capacity, calculating the 0.1C specific capacity of the positive electrode material based on the first discharge capacity, and calculating the first charge and discharge efficiency of the battery, i.e., the first efficiency, according to the following formula: first charge and discharge efficiency = (first discharge capacity / first charge capacity) * 100%.

[0117] Then repeat the above charge and discharge process once at 1C current, record the 2nd charge capacity and 2nd discharge capacity, and calculate the 1C specific capacity of the positive electrode material with the 2nd discharge capacity.

[0118] Table 2

[0119]

[0120] First, the electrical properties and compaction density of the lithium iron phosphate positive electrode material in Examples 1-3 are effectively improved. Since Example 1-3 performs one dry mixing and one wet grinding, compared with the process of only one wet grinding in Comparative Example 1, the powder compaction density of the lithium iron phosphate positive electrode material in Example 1-3 is greatly improved. Specifically, the powder compaction density of the lithium iron phosphate positive electrode material in Example 1-3 is 2.55g / cc, 2.52g / cc and 2.57g / cc, respectively, while the powder compaction density of the lithium iron phosphate positive electrode material in Comparative Example 1 is only 2.38g / cc; in addition, the powder resistivity of the lithium iron phosphate positive electrode material in Example 1-3 is less than that in Comparative Example 1. Compared with Comparative Example 2, the powder compaction density, resistivity and electrical properties of Example 1-3 are similar, but Comparative Example 2 adopts a two-time grinding method, which is complex in process, high in energy consumption and low in production capacity. Unlike Comparative Example 2, Example 1-3 adopts dry mixing to reduce production energy consumption and cost.

[0121] Among them, compared with Example 3, Examples 1-2 have better overall comprehensive performance such as powder compaction density, resistivity and electrical properties. This is because the particle size D50 in Examples 1-2 is all between 0.4μm and 0.6μm, while the particle size D50 of the secondary mixture in Example 3 is 0.68μm. Although the powder compaction density is slightly increased, its electrical properties are reduced due to the increase in the lithium ion transmission path.

[0122] Secondly, the carbon content of the lithium iron phosphate positive electrode materials in Examples 1-3 is within a suitable range, which is conducive to the uniform distribution of the carbon coating layer, thereby improving the conductivity and structural stability of the lithium iron phosphate positive electrode materials.

[0123] In addition, the lithium iron phosphate precursor and the lithium iron phosphate positive electrode material in Example 1 and the lithium iron phosphate positive electrode material obtained in Comparative Examples 1-2 were observed using a scanning electron microscope (SEM).

[0124] Figure 3 is a SEM image of the lithium iron phosphate precursor in Example 1, Figure 4 is a SEM image of the lithium iron phosphate positive electrode material in Example 1, Figure 5 is a particle size distribution diagram of the lithium iron phosphate positive electrode material in Example 1. Figure 3 , Figure 4 and Figure 5 It can be seen that the particle size of the lithium iron phosphate precursor after dry mixed sintering is relatively large, and a double peak appears in the particle size distribution after wet grinding, realizing particle size grading. The particles of the lithium iron phosphate positive electrode material in Example 1 obtained by sintering form a grading effect, which is beneficial to achieving an increase in the compaction density of the lithium iron phosphate positive electrode material.

[0125] Figure 6 is the SEM image of the lithium iron phosphate positive electrode material in Comparative Example 1. Figure 4 It can be seen that the grading effect of the lithium iron phosphate positive electrode material in Example 1 is better. This is because Example 1 forms a particle size grading after wet grinding, and the compaction of the size particle grading is improved after the secondary sintering. However, after the first sintering, the number of primary particles above 1 μm in Comparative Example 1 is small, the particle size grading effect is poor, and therefore the compaction is low.

[0126] Figure 7 is the SEM image of the lithium iron phosphate positive electrode material in Comparative Example 2, and Figure 4 In comparison, the particle size and large and small particle grading effects are similar, but the preparation method of comparative example 2 consumes more energy and has lower production capacity.

[0127] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.

Claims

1. A method for preparing a lithium iron phosphate positive electrode material, characterized in that: include: dry-mixing a phosphorus source, an iron source, a lithium source and a first carbon source to obtain a primary mixture; Sintering the primary mixture to obtain a lithium iron phosphate precursor; The lithium iron phosphate precursor, the second carbon source and the solvent are mixed and ground to obtain a secondary mixture; as well as The secondary mixed material is subjected to secondary sintering to obtain the lithium iron phosphate positive electrode material.

2. The method for preparing the lithium iron phosphate positive electrode material according to claim 1, characterized in that: The dry mixing is carried out by using a plowshare mixer.

3. The method for preparing the lithium iron phosphate positive electrode material according to claim 2, characterized in that: The mixing conditions of the plowshare mixer include at least one of the following features: (1) Mixing time is 0.5h~4.0h; (2) The frequency of the main motor of the plow is 25Hz~50Hz; (3) The frequency of the plow blade is 10Hz to 50Hz.

4. The method for preparing a lithium iron phosphate positive electrode material according to claim 1, characterized in that: The particle size D50 of the secondary mixture is 0.4 μm to 0.6 μm; The grinding is carried out in two steps. In the first step, the secondary mixture is ground to a particle size D50 of 1.0 μm to 2.0 μm. In the second step, the ground product of the first step is further ground to a particle size D50 of 0.4 μm to 0.6 μm.

5. The method for preparing the lithium iron phosphate positive electrode material according to claim 1, characterized in that: The particle size distribution of the secondary mixture satisfies the following relationship: 0.90≤(D90-D10) / D50≤1.

70.

6. The method for preparing a lithium iron phosphate positive electrode material according to claim 1, characterized in that: The mass percentage of the first carbon source in the primary mixture is 4% to 8%; The mass percentage of the second carbon source in the secondary mixture is 4% to 20%.

7. The method for preparing a lithium iron phosphate positive electrode material according to claim 1, characterized in that: Doping materials are also added to the primary mixture and / or the secondary mixture, and the doping materials include at least one of titanium dioxide, tetrabutyl titanate, magnesium oxide, magnesium acetate, magnesium hydroxide, magnesium nitrate, zirconium nitrate, zirconium hydroxide, zirconium oxide and niobium pentoxide.

8. The method for preparing a lithium iron phosphate positive electrode material according to claim 1, characterized in that: The conditions of the primary sintering include: a sintering temperature of 600°C to 750°C, a sintering time of 3h to 15h, and a heating rate of 2°C / min to 5°C / min; The conditions of the secondary sintering include: a sintering temperature of 700° C. to 800° C., a sintering time of 3 h to 15 h, and a heating rate of 2° C. / min to 5° C. / min.

9. A lithium iron phosphate positive electrode material, characterized in that: The lithium iron phosphate positive electrode material is prepared by the method for preparing the lithium iron phosphate positive electrode material according to any one of claims 1 to 8.

10. An electrochemical device, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet comprises the lithium iron phosphate positive electrode material as claimed in claim 9.

Citation Information

Patent Citations

  • Preparation method of high-compaction high-rate high-voltage lithium cobalt oxide positive electrode material

    CN113247963A

  • Preparation method and application of lithium ferric manganese phosphate positive electrode material

    CN115172681A

  • Preparation method of ultra-high-compaction lithium iron phosphate positive electrode material and lithium battery

    CN118373398A

  • Co-embedded high-compaction lithium iron phosphate positive electrode material and preparation method thereof

    CN118398792A

  • Positive active material for lithium secondary battery and method of preparing the same and lithium secondary battery comprising the same

    KR102684130B1

Cited By

  • Lithium iron phosphate material and preparation method thereof, positive pole piece and secondary battery

    CN120757092A

  • Secondary sintering process method for improving compaction density of lithium iron phosphate and application of secondary sintering process method

    CN121317679A

  • Lithium iron phosphate positive electrode material and preparation method therefor, and electrochemical device

    WO2026067387A1

  • Lithium iron phosphate positive electrode material and preparation method therefor, and electrochemical device

    WO2026157291A1